2015
DOI: 10.1007/s00464-015-4377-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between gastric pouch and weight loss after laparoscopic sleeve gastrectomy

Abstract: No statistical correlation was found between the volume of the gastric pouch and weight loss (percent EBL) after LSG in symptomatic or with unsatisfactory weight loss patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…In the same way, Barbiero et al recently reported that the presence and the volume of a saccular dilatation of the cranial portion of the sleeve assessed by upper GI studies more than 1 year after surgery did not affect weight loss [7]. Braghetto et al did not find any association between the increase in residual gastric capacity at 2 years, assessed by barium or CT scan, and weight regain [7]. Karcz et al presented the results of banded LSG with a silicone ring that has been described as an option to counteract sleeve dilatation, but they failed to demonstrate an influence on weight loss in the first year of follow-up [20].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In the same way, Barbiero et al recently reported that the presence and the volume of a saccular dilatation of the cranial portion of the sleeve assessed by upper GI studies more than 1 year after surgery did not affect weight loss [7]. Braghetto et al did not find any association between the increase in residual gastric capacity at 2 years, assessed by barium or CT scan, and weight regain [7]. Karcz et al presented the results of banded LSG with a silicone ring that has been described as an option to counteract sleeve dilatation, but they failed to demonstrate an influence on weight loss in the first year of follow-up [20].…”
Section: Discussionmentioning
confidence: 88%
“…Data are presented as arithmetic means ± standard error of mean early weight loss failure following LSG. In the same way, Barbiero et al recently reported that the presence and the volume of a saccular dilatation of the cranial portion of the sleeve assessed by upper GI studies more than 1 year after surgery did not affect weight loss [7]. Braghetto et al did not find any association between the increase in residual gastric capacity at 2 years, assessed by barium or CT scan, and weight regain [7].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Weight loss after LSG appears to be multifactorial, despite volume restriction being the key factor. 19 , 20 The impact of residual sleeve volume after LSG on weight loss has been investigated. A high residual gastric volume (RGV) three years after LSG was a risk factor for failure.…”
Section: Discussionmentioning
confidence: 99%
“…We have encountered a number of studies that were evaluating the gastric specimen measurements (2,4,5,13). Most of the studies in the literature have taken into consideration that the gastric specimen volume as an independent factor affecting the EWL% (4-6).…”
Section: Discussion Discussionmentioning
confidence: 99%